Chlorpyrifos and lambda cyhalothrin-induced oxidative stress in human erythrocytes: In vitro studies. (April 2017) - Deeba, Farah; Raza, Irum; Muhammad, Noor; Rahman, Hazir; ur Rehman, Zia; Azizullah, Azizullah; Khattak, Baharullah; Ullah, Farman; Daud, MK
Pesticides are one of the most potentially harmful chemicals introduced into the environment, and their adverse impacts on non-target organisms can be significant. The present study was conducted to shed light on effects of locally used insecticides chlorpyrifos (CPF) and lambda cyhalothrin (LCT) on oxidative stress biomarkers in human erythrocytes. The activity of catalase (CAT), superoxide dismutase (SOD), and protein contents as well as the levels of malondialdehyde (MDA) and osmotic fragility (OF) were measured in human erythrocytes exposed to CPF at concentrations of 0, 100, 500, 1000, and 2000 ppm and LCT at concentrations of 0, 100, 300, 600, and 800 ppm for 1 h and 3 h at 37°C. MDA levels and OF of erythrocytes were significantly higher in erythrocytes incubated with CPF and LCT at increasing concentrations of both insecticides and increased incubation time. However, erythrocyte CAT and SOD activities were decreased at all concentrations of CPF and LCT tested. Protein oxidation products were decreased at lower doses of CPF (100 and 500 ppm); at higher doses (1000 and 2000 ppm), total protein content was increased compared with control. In contrast LCT was associated with decreased in protein contents at all the concentrations. These results clearly demonstrated that CPF and LCT can induce oxidative stress in human erythrocytes ( in vitro ).